The Influence Of Customer Service Quality On Financial Expectations With Roq Approach (Case Study: X Maternity Hospital in Sidoarjo) - Reiny Ditta Myrtanti; Sujianto (Department of Industrial Engineering - Universitas Yudharta Pasuruan, 2022)
The tight competition between Maternity Hospital services in Sidoarjo Regency is marked by the increasing number of couples of childbearing age and family planning participants, as well as the high rate of pregnant women and the birth of babies, becoming a big challenge for the Maternity Hospital management to be able to know, understand and fulfill the needs and desires of consumers. patients) so that customer satisfaction can be met, for example fast, accurate, friendly service, at an adequate price. This is the reason for the management to make improvements from the quality program that has been run previously. However, not all quality improvement programs carried out will provide benefits for the management, because many of these improvement programs are wasteful after being implemented. This is because the management does not focus on the quality improvement program that will be implemented, that is, it does not determine which variables are the most influential for the quality improvement program.At this X Maternity Hospital, complaints or complaints are often found from patients about the services provided, for example at the counter service which is less prompt in providing services, and the inconvenience of services in the inpatient room. The data was obtained from the Maternity Hospital management through the available suggestion/vote box, then used as a basis/reference for making a questionnaire as a follow-up to the problems that arose. Therefore, this study discusses the Maternity Hospital's efforts in planning a quality improvement program that is in accordance with the wishes and needs of patients by selecting and determining the variables or dimensions that have the most influence on the quality improvement program to be carried out, as well as assessing its financial feasibility by using the Return on Quality (ROQ) approach.From the application of ROQ at a Maternity Hospital X in Sidoarjo Regency, two quality improvement programs were determined from the two dimensions of the X Maternity Hospital service process, they are beds and patient registration. The ROQ value of each program based on the discount rate (5%, 10%, 15%) is 1.54; 0.99; 0.49 for the inpatient room service process, and 1.25; 0.61; 0.24 for the process of front office and administration services. For this reason, the dimension that is the focus of the quality improvement program is the inpatient room service process with the dimensions of the bed.